2007
DOI: 10.1534/genetics.106.068171
|View full text |Cite
|
Sign up to set email alerts
|

Mlh1 Deficiency in Zebrafish Results in Male Sterility and Aneuploid as Well as Triploid Progeny in Females

Abstract: In most eukaryotes, recombination of homologous chromosomes during meiosis is necessary for proper chromosome pairing and subsequent segregation. The molecular mechanisms of meiosis are still relatively unknown, but numerous genes are known to be involved, among which are many mismatch repair genes. One of them, mlh1, colocalizes with presumptive sites of crossing over, but its exact action remains unclear. We studied meiotic processes in a knockout line for mlh1 in zebrafish. Male mlh1 mutants are sterile and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
64
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 35 publications
11
64
0
Order By: Relevance
“…1A and D). We recently showed that this mutation results in full loss-of-function of MLH1 and causes a strong meiotic phenotype (35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A and D). We recently showed that this mutation results in full loss-of-function of MLH1 and causes a strong meiotic phenotype (35).…”
Section: Resultsmentioning
confidence: 99%
“…Genotyping was done either by PCR amplification and resequencing or by using KASPAR genotyping technology (Kbioscience). The mlh1 (hu1919) mutants were generated as described previously (35).…”
Section: Pcrmentioning
confidence: 99%
“…Morphometric analysis of testis of control and E 2 -exposed fish was conducted according to Feitsma et al (2007) with some modifications. Volume fractions of various testicular tissue components were determined as the area of cysts containing cells normalized by the total area of testis analysed to obtain a percentage of total tissue for each component.…”
Section: Histologymentioning
confidence: 99%
“…In zebrafish, MLH1 mutants fail to form chiasmata and display univalents in metaphase I resulting in arrest of spermatogenesis and subsequent infertility. Females produce aneuploid gametes, an indication of chromosomal missegregation (Feitsma et al, 2007).…”
Section: Introductionmentioning
confidence: 99%